Porous high-entropy alloys as efficient electrocatalysts for water-splitting reactions - Adewale K. Ipadeola (12699590) (2022)
Porous high-entropy alloys (HEAs) have emerged as promising electrocatalysts for water-splitting reactions, owing to their rich dissimilar active sites, elemental diversity, and multiple functionalities. The rational design of HEAs for water-splitting attracted great interest in improving their current performance, so it is essential to provide timely updates on this field. This review emphasizes the preparation methods of porous HEAs and the effect of their salient features like high configurational entropy, cocktail effect, lattice distortion, and sluggish diffusion on oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). This mini-review also provides some insights into the current limitations and future perspectives to direct research on the development of ideal HEAs for OER and HER. Other Information Published in: Electrochemistry Communications License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.elecom.2022.107207